Comparative Analysis of the Implementation of Ethnopedagogy in Elementary Art Learning in Indonesia with Various Global Contexts - Muhammad Syafruddin Akmal; Muhammad Suyudi (EDUKASI, 2026)
The study aims to comparatively analyze ethnopedagogical practices in art education across Indonesia, Europe, America, Africa, and Asia by identifying their similarities, differences, and educational characteristics. A comparative literature review was employed using academic articles, international journals, and educational reports published within the last ten years. The findings indicate that ethnopedagogical art education is implemented through diverse cultural forms adapted to local contexts. In Indonesia, learning emphasizes batik, carving, weaving, and other traditional arts; Europe utilizes art as a medium for intercultural understanding and multicultural integration; America highlights indigenous and community-based artistic traditions; Africa incorporates communal values through Ubuntu-based art practices and cultural symbols; while Asia integrates traditional arts, cultural heritage, and character education. Despite contextual differences, all regions share a common objective of using art education to strengthen cultural identity, transmit moral values, and enhance creativity. The study concludes that ethnopedagogy remains a significant framework for developing culturally responsive and sustainable art education in contemporary society.